2020
DOI: 10.1101/2020.11.26.400184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-millisecond conformational dynamics of the A2A adenosine receptor revealed by single-molecule FRET

Abstract: The complex pharmacology of G-protein-coupled receptors (GPCRs) is defined by their multi-state conformational dynamics. Single-molecule Förster Resonance Energy Transfer (smFRET) is well-suited to quantify dynamics for individual protein molecules, however, its application to GPCRs is challenging; therefore, smFRET has been limited to studies of interreceptor interactions in cellular membranes and receptors in detergent environments. Here, we performed smFRET experiments on functionally active human A2A adeno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 82 publications
(138 reference statements)
3
19
0
Order By: Relevance
“…Using single-molecule total internal reflection fluorescence (TIRF) imaging, we observed relatively slower (k ex % 10 s À1 ) exchange processes in A 2A AR with a fluorophore covalently attached to helix 7 at the intracellular surface. Our data complement other A 2A AR studies that investigated relatively faster timescales using single-molecule Fo ¨rster resonance energy transfer (FRET), which measured ligand efficacy-dependent changes for sub-millisecond to $3 millisecond molecular motions of A 2A AR in detergent micelles (Fernandes et al, 2021) and in lipid nanodiscs (Maslov et al, 2020). In the present study, measurements of slower exchange processes provide an exciting window into A 2A AR function-related conformational dynamics.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Using single-molecule total internal reflection fluorescence (TIRF) imaging, we observed relatively slower (k ex % 10 s À1 ) exchange processes in A 2A AR with a fluorophore covalently attached to helix 7 at the intracellular surface. Our data complement other A 2A AR studies that investigated relatively faster timescales using single-molecule Fo ¨rster resonance energy transfer (FRET), which measured ligand efficacy-dependent changes for sub-millisecond to $3 millisecond molecular motions of A 2A AR in detergent micelles (Fernandes et al, 2021) and in lipid nanodiscs (Maslov et al, 2020). In the present study, measurements of slower exchange processes provide an exciting window into A 2A AR function-related conformational dynamics.…”
Section: Introductionsupporting
confidence: 77%
“…In a recent report of single-molecule FRET of A 2A AR in detergent micelles containing LMNG and CHS, ligand-depending shifts and broadening of smFRET distributions were interpreted to suggest exchange between inactive and active conformations of A 2A AR that occurred on a timescale of $3 ms or k ex R $30-40 s À1 (Fernandes et al, 2021). In a separate study, Maslov et al reported observations of exchange processes on a similar timescale of sub-millisecond to low millisecond fluctuations with A 2A AR in nanodiscs containing POPC and POPG lipids (Maslov et al, 2020). Both the Fernandes et al and Maslov et al studies utilized a diffusion-based experimental design in which the observation of FRET signals depends on the rate of diffusion of the receptors in aqueous solutions.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we used the β 1 AR-E construct to characterise the conformational properties of the active state in solution by NMR spectroscopy. We labelled β 1 AR-E with 13 C methyl methionine, facilitating examination of the NMR response to full agonist on the natively occurring methionine positions M153 34.57 (IL2), M178 4.62 (EL2), M223 5.54 (TM5), M283 6.28 (TM6), and M296 6.41 (TM6) (Fig. 2a) assigned in previous work using β 1 AR-W 20 .…”
Section: Resultsmentioning
confidence: 99%
“…2a) assigned in previous work using β 1 AR-W 20 . We assessed conformational changes of the receptor upon isoprenaline addition through 2D 1 H- 13 C HMQC methionine NMR shift correlation experiments and used peak changes in both dimensions compared to the apo state spectrum to inspect differences in conformations and dynamics (Supplementary Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation